ARTIFICIAL INTELEGENCE DALAM SISTEM INFORMASI MANAJEMEN DAN KINERJA BERKELANJUTAN - Ari Riswanto; R. Edy Rachmadi (JURNAL LENTERA BISNIS, 2023)
The purpose of this study is to determine the extent to which Artificial Intelligence (AI) variables can moderate the influence between Management Information Systems and Sustainable Performance in Small and Medium Enterprises (SMEs) in West Java - Indonesia. The approach using quantitative descriptive methods through simple linear regression analysis with SPSS was used in this study while for analysis using Structural Equation Modeling (SEM) with Coefficient Product Analysis Strategy: Simple Moderation Model, with a sample of 209 respondents, namely SMEs in West Java Province, Indonesia. The results of the study show that the variable Artificial Intelligence can moderate the influence between Management Information Systems and Sustainable Performance in Small and Medium Enterprises (SMEs) in West Java - Indonesia. In addition, the Management Information System has a positive effect on sustainable performance. The implication of the results of this study is that the performance of SMEs can be improved by increasing the involvement of SMEs in managing their accounting information systems. The value of novelty in this study is that this study uses Artificial Intelligence variables that no one has conducted the same research, besides that IA is used to measure the extent of involvement in the influence of Management Information Systems and Sustainable Performance in small and medium enterprises (SMEs). Further researchers can carry out further research by developing the use of other variables in larger and wider business entities and industries as research samples.Key words: Artificial Intelligence (AI), Management Information Systems, Sustainable Performance, SMEs.